2011
DOI: 10.3855/jidc.2249
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus metrics for patients in Saudi Arabia

Abstract: Introduction: The World Health Organization recommends essential measures to "combat drug resistance", including instituting surveillance "everywhere". Standardized metrics are crucial for reliable surveillance. Studies publish metrics with varying definitions for multi-drug resistant organisms (MDRO). The Society for Healthcare Epidemiology of America (SHEA) and the Healthcare Infection Control Practices Advisory Committee (HICPAC) proposed standardized metrics for MDRO for consistent reporting, identifying h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [26,27]. Nevertheless, the current finding was consistent with the local MRSA rates obtained from HAI specimens (mainly wound), which ranged between 16 and 57% [26]. For VRE, the current rates (13%) was comparable to recent reports from Saudi Arabia [28].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [26,27]. Nevertheless, the current finding was consistent with the local MRSA rates obtained from HAI specimens (mainly wound), which ranged between 16 and 57% [26]. For VRE, the current rates (13%) was comparable to recent reports from Saudi Arabia [28].…”
Section: Discussionsupporting
confidence: 84%
“…For example, MRSA rates was 30% in the current study compared with more than 40% in USA [8,9], Europe [5], and Asia [24,25]. In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [26,27]. Nevertheless, the current finding was consistent with the local MRSA rates obtained from HAI specimens (mainly wound), which ranged between 16 and 57% [26].…”
Section: Discussionmentioning
confidence: 76%
“…In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [33,34]. Nevertheless, the current finding was consistent with the local MRSA rates obtained from HAI specimens (mainly wound), which ranged between 16% and 57% [33]. For VRE, the current rates (13%) was comparable to recent reports from Saudi Arabia [35].…”
Section: Discussionsupporting
confidence: 84%
“…For example, MRSA rates was 30% in the current study compared with more than 40% in USA [14,15], Europe [5], and Asia [31,32]. In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [33,34]. Nevertheless, the current finding was consistent with the local MRSA rates obtained from HAI specimens (mainly wound), which ranged between 16% and 57% [33].…”
Section: Discussionmentioning
confidence: 76%
“…12 A survey by Lowe et al 13 demonstrated large variation in infection control practices, such as admission screening and contact precautions, for ESBL-producing organisms and CRE in Canadian hospitals. While these recent studies have focused on single countries or regions, most often in developed countries, [12][13][14] a global picture of infection prevention practices for MDRO prevention has thus far been lacking. In our survey, we found similar variability in practices and procedures; however, we did not Inadequate resources/ staffing (n = 12) NOTE.…”
Section: Resultsmentioning
confidence: 99%